Language Games in Developing Speaking Skills (Rupandehi Campus Journal, 2022)
Learning language is bored when learners do not change their learning habits, such as writing words on paper, repeating the same thing in a bored manner, trying to learn by heart or learning passively through the teacher’s explanations. The article tries to show that the students are very attentive and keen to learn if they are presented subject matters with games and interactive way. To help students find language classes, all the aspects and skills and vocabulary in particular more interesting, and to achieve more from games, this article is very beneficial. This article also tries to focus on the effectiveness of using games in the classroom. It also indicates the advantages of language games in teaching all the aspects of language. At last it points out the effective language games that are beneficial in language classroom.